PROJECT-BASED LEARNING AND NEED ANALYSIS OF ESP IN DEVELOPING LANGUAGE SKILLS FOR BROADCASTING AND FILM STUDENTS - Gaffar, Muhammad Andriana; Rahmawati, Elmira; Neliasari, Putri Nesi (University of Kuningan, 2024)
One-way communication, where teachers dominate classroom discourse, can significantly hinder effective teaching and learning. This limited interaction often stems from students' low willingness to communicate, often due to fear of judgment or ridicule for making mistakes. This reluctance to engage can negatively impact their academic performance. Therefore, it becomes the teacher's responsibility to identify and implement appropriate methods to address this issue. Cooperative learning emerges as a promising approach, as it centers on student-focused group activities. By employing this method, student interaction can be enhanced, reducing anxiety and fostering the development of essential social skills. This research aims to study the effectiveness of cooperative learning in promoting willingness to communicate orally. This research employed a quantitative methodology. The gathered data was meticulously tabulated and analyzed using paired t-tests to determine the significance of cooperative learning in improving students' oral communication readiness. Additionally, independent t-tests were conducted to examine any differences between the experimental and control classes. The study involved a sample of students from SMK Plus Darussurur. The results of the paired t-tests revealed a positive influence of cooperative learning on students' willingness to communicate orally. Furthermore, a significant difference in post-test scores was observed between the experimental and control classes. These findings provide compelling evidence that cooperative learning fosters positive interactions, which in turn cultivate increased willingness to communicate orally. By encouraging active student participation and collaboration, cooperative learning creates a supportive environment where students feel empowered to express themselves without fear of judgment, leading to improved academic.